Pengaruh PBL Berorientasi One Stay Another Stray terhadap Keterampilan Komunikasi Siswa SMAN 1 Batusangkar: Penelitian - Alvis Aldora Irwanto; Muhyiatul Fadilah; Fitri Arsih; Ria Anggriyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study was to examine the effect of using problem-based learning oriented One Stay Another Stray on Communication Skills of Students of SMAN 1 Batusangkar. Currently, the communication skills of students in the school are still relatively low. This research adopts experimental method with pre-experiment design. The research population includes all students of class XI Phase F SMAN 1 Batusangkar, with samples from class XI F 10. Data were collected through essay tests given in the form of pretests at the beginning of the study and posttests at the end of the study. Data analysis was carried out using normality test, homogeneity test, and hypothesis test with the help of SPSS 20 software. The results showed that students' communication skills at posttest were higher than at pretest. Hypothesis testing shows a 2- tailed significance value <0.05, which is 0.00. Thus, it can be concluded that the use of problem-based learning oriented One Stay Another Stray has a positive impact on students' communication skills at SMAN 1 Batusangkar.